BOOK REVIEW: STUDI KITAB RISA>LAH AHL AS-SUNNAH WA AL- JAMA>’AH: FI> HADIS AL-MAUTA WA ASYRA>T} AS-SA>’AH WA BAYA>NI MAFHU>M AS-SUNNAH WA AL-BID’AH KARYA K.H. HASYIM ASY’ARI - Khikmatiar, Azkiya (Mazalat: Jurnal Pemikiran Islam, 2024)
This article discusses the study of the book Risa>lah Ahl as-Sunnah Wa al-Jama>’ah which is the work of one Indonesian scholar, namely K.H. Hasyim Ash'ari. There are several important issues that will be studied, namely the biography of K.H. Hasyim Asy'ari, the naming and background of the writing of his book, his method and systematics, the source and quality of the hadith in his book, the characteristics and examples of the hadith, as well as its strengths and weaknesses. This research is a qualitative research with a library research model. The results of this research is that the book Risa>lah Ahl as-Sunnah Wa al-Jama>’ah is a book that contains explanations on hadiths about death, signs of the end times and the paradigmatic differences between sunnah and heresy by using the method and the typical systematics of K.H. Hasyim Ash'ari.